Do We Expect Women to Look Happier Than They Are? A Test of Gender-Dependent Perceptual Correction. (February 2018) - Steephen, John Eric; Mehta, Samyak Raj; Bapi, Raju Surampudi
Feminine facial features enhance the expressive cues associated with happiness but not sadness. This makes a woman look happier than a man even when their smiles have the same intensity. So, to correctly infer the actual happiness of a woman, one would have to subtract the effect of these facial features. We hypothesised that our perceptual system would apply this subtraction for women, but not for men. This implies that this female-specific subtraction would cause one to infer a man to be happier than a woman if both are matched for facial appearance and expression intensity. We tested this using androgynous virtual faces with equal expression intensity. As predicted, happy men were inferred to be happier than happy women, but sad men were not inferred to be sadder than sad women, supporting our hypothesis of a gender- and emotion-specific perceptual correction.